Cambios en las medidas antropométricas en escolares de 6 a 10 años de edad suplementados con leche de vaca versus leche de vaca fortificada con micronutrientes en una escuela en la periferia de Quito - Cocha Millingalle, Ignacio Santiago (2016)
The present study had as objective to determine the changes in anthropometric measures before and after supplementation with fortified milk of cow with micronutrients zinc, iron and vitamin A versus milk of cow in school children of 6 to 10 years old at a school in the outskirts of Quito for a period of six months. The study was experimental, qualitative and transversal type. He was evaluated at 328 children at a school in the outskirts of Quito, he divided them into two groups, Group A and group b to each were supplemented with milk of cow and the other with fortified milk of cow. Weight and height measurements were taken and we calculated the body mass index, compared with tables of growth and development of the World Health Organization. The results of the students of the group show a decrease of overweight, while in Group B existed a children increase in overweight and obesity. 71% of schoolchildren were within the normal range of body mass index and only 29% were overweight (overweight and obesity), they have 22% overweight and 7% obesity.